The effect of land access on youth employment and migration decisions: Evidence from rural Ethiopia - Kosec, Katrina; Ghebru, Hosaena; Holtemeyer, Brian; Mueller, Valerie; Schmidt, Emily (International Food Policy Research Institute, 2017)
In Ethiopia, there are two binding forces (push and pull) that deserve attention when it comes to youth occupational and spatial mobility choices and the national land use and transfer policy. On the one hand, the fact that the land rental market in Ethiopia is supply constrained due to market and policy distortions marginalizes youth and serves as a push factor leading them to look elsewhere for a livelihood strategy. On the other hand, the regulatory conditions and restrictions attached to land use and inheritance rights may serve as a pull factor and force youth to be tied to the rural and/or farming sector. Our study thus aims to explore how youth land access (both inheritance and market-based) affects their migration and employment decisions. We explore this question in the context of rural Ethiopia using panel data from 2010 and 2014. We find that larger expected land inheritances significantly lower the likelihood of long-distance permanent migration and of permanent migration to urban areas during this time. Inheriting more land is also associated with a significantly higher likelihood of employment in agriculture and a lower likelihood of employment in the nonagricultural sector. Conversely, the decision to attend school is unaffected. These results appear to be most heavily driven by males and by the older half of our youth sample. We also find several mediating factors matter. Land inheritance plays a much more pronounced role in predicting rural-to-urban permanent migration and nonagricultural-sector employment in areas with less vibrant land markets and in relatively remote areas (those far from major urban centers). Overall, the results reaffirm the notion that push factors dominate pull factors in dictating occupational and migration decisions in Ethiopia and highlight youth preferences to use migration or non-agricultural employment as a last resort after exhausting other means of accessing land, such as temporary land rental.